2010
DOI: 10.1016/j.jconrel.2009.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Improved Tat-mediated plasmid DNA transfer by fusion to LK15 peptide

Abstract: The use of cell penetrating peptides (CPPs), such as Tat-derived peptide, to deliver DNA into cells is limited as evidenced by the low transfection efficiency of their DNA complexes. Here, we demonstrate that covalent attachment of membrane active peptide LK15 to Tat peptide improves gene transfer. Our results demonstrate that Tat peptide was able to form complexes with DNA, but their transfection efficiency was insufficient as assessed by luciferase assay. The attachment of LK15 to Tat significantly improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 34 publications
(47 reference statements)
4
42
0
Order By: Relevance
“…E.g. the efficiency of cargo introduction by TAT into HT29 [34] and BR2 into HCT116 cells was reported [35]. Our study is the first focused on the effects of TP, TP10 and their biotinylated derivates on cell viability and large protein cargo delivery into early-staged HT29 and metastatic colorectal cancer HCT116 cells.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…E.g. the efficiency of cargo introduction by TAT into HT29 [34] and BR2 into HCT116 cells was reported [35]. Our study is the first focused on the effects of TP, TP10 and their biotinylated derivates on cell viability and large protein cargo delivery into early-staged HT29 and metastatic colorectal cancer HCT116 cells.…”
Section: Discussionmentioning
confidence: 77%
“…The main goal for all CPPs in cancer cell studies is to deliver anticancer agents into cytoplasm/nucleus without causing damage to the cell membrane. Recently, siRNA [41], plasmid DNA [34], PNA [42] or PMO (Morpholino oligomers) [43] agents have been intensively studied in order to trigger specific cellular responses via up or down regulation of gene expression. Moreover, CPPs were used for the induction of direct cellular death by the introduction of doxorubicin [44] or anti-cancer drug paclitaxel [45] into the cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, CPPs have become a new tool for gene delivery, because it has characteristics of low toxicity, immunogenicity, insertional mutagenesis and easy operation (Choi et al, 2006;Saleh et al, 2010;Song et al, 2010). In this report, we initially demonstrated that HR9-FITC is able to translocate itself into ciliated organism.…”
Section: Discussionmentioning
confidence: 90%
“…The mechanisms of CPP-mediated cellular uptake essentially influence the efficiencies and biological activities of delivered cargoes in cells (Nakase et al, 2010). Moreover, it was noted that the additional attachment of Mu DNA-binding domain (Xavier et al, 2009), LK15 peptide (Saleh et al, 2010) or stearylated nuclear localization signal peptide (Wang et al, 2011) to CPP, becoming Tat-NLSMu, Tat-LK15 or STR-NLS-R8 fusion peptides, significantly improved DNA transfer in cells or tumors. Interestingly, CPPs covalently combine with not only peptides but also noncovalently link with other devices can enhance DNA transfection efficiency.…”
Section: Discussionmentioning
confidence: 99%